Combinatory Approaches Targeting Cognitive Impairments and Memory Enhancement: A Review - Gupta, Varun S.; Kale, Pravin Popatrao (Current Drug Targets, 2023)
The objective of this paper is to look at how natural medicines can improve cognition and memory when used with sildenafil, a popular erectile dysfunction medicine that also has nootropic properties. Newer treatment strategies to treat the early stages of these diseases need to be developed. Multiple factors lead to complex pathophysiological conditions, which are responsible for various long-term complications. In this review, a combination of treatments targeting these pathologies is discussed. These combinations may help manage early and later phases of cognitive impairments. The purpose of this article is to discuss a link between these pathologies and a combinational approach with the objective of considering newer therapeutic strategies in the treatment of cognitive impairments. The natural drugs and their ingredients play a major role in the management of disease progression. Additionally, their combination with sildenafil allows for more efficacy and better response. Studies showing the effectiveness of natural drugs and sildenafil are mentioned, and how these combinations could be beneficial for the treatment of cognitive impairments and amnesia are summarised. Furthermore, preclinical and clinical trials are required to explore the medicinal potential of these drug combinations.
Keywords: neurodegenerative diseases